(untitled) (Research, Society and Development, 2021)
The content of Molecular Geometry is viewed with difficulty by most students. This difficulty is often linked to the way the subject is approached in the classroom. It is known that digital technologies are increasingly inserted in the students’ daily lives and that they can be used to promote a favorable environment for learning, helping the teacher in the classroom. In order to facilitate understanding and promote meaningful learning, the present work suggests the use of the activity proposed by the augmented reality application Mirage-Molecular Geometry, where the student has the opportunity to understand the geometry of some molecules through the observation of its structure from different angles. In addition, augmented reality promotes education dynamically, enabling students to actively participate in the construction of their knowledge. Thus, it is expected that the presented practice promotes an improvement in the learning process, making it more effective and attractive.